El Excentrico, 1971-07-20 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
July 20, 1971 [20 de julio de 1971]. No volume or issue number. Cover has a photograph of a woman being crowned by another, and a group photograph of the women with ten men in suits on a bridge. The photographs appear to have been taken at the Japanese Friendship Garden in San Jose, California. They are for the Club San Felipe 13th Anniversary Ball and Buffet.